THE ROLE OF MAQASID AL-SHARIAH IN ENHANCING THE FINANCIAL WELL-BEING OF FISABILILLAH ZAKAT RECIPIENTS IN HIGHER EDUCATION - Mohd Adnan, Amni; Abdullah, Azwan; Muhammad, Mohd Zulkifli (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
University students, particularly those from low-income households, often face financial challenges that negatively impact their academic performance, mental health, and overall well-being. In Malaysia, fisabilillah zakat serves as a vital financial aid mechanism for students in higher education institutions. However, evidence shows that while zakat alleviates short-term financial pressure, many recipients lack the necessary financial literacy and discipline to manage the assistance effectively. This conceptual paper proposes Maqasid al-Shariah as the higher objectives of Islamic law as a guiding framework for financial management among zakat recipients. By integrating the dimensions of religion, life, intellect, lineage, and wealth into financial decision-making, students can transform zakat aid into sustainable financial well-being, academic resilience, and personal development. Employing a qualitative conceptual approach, this paper develops a model to explain how students can apply Islamic principles to financial practices, thereby enhancing the long-term effectiveness of zakat assistance in higher education.